2012
DOI: 10.1371/journal.pone.0035777
|View full text |Cite
|
Sign up to set email alerts
|

Chilling-Dependent Release of Seed and Bud Dormancy in Peach Associates to Common Changes in Gene Expression

Abstract: Reproductive meristems and embryos display dormancy mechanisms in specialized structures named respectively buds and seeds that arrest the growth of perennial plants until environmental conditions are optimal for survival. Dormancy shows common physiological features in buds and seeds. A genotype-specific period of chilling is usually required to release dormancy by molecular mechanisms that are still poorly understood. In order to find common transcriptional pathways associated to dormancy release, we analyze… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
54
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 73 publications
(63 citation statements)
references
References 64 publications
6
54
0
Order By: Relevance
“…(1977) found that short stratification promoted the production of morphological lesions on peach leaves. An in vitro culture experiment on peach seeds showed that seedlings grew with a dwarf phenotype when the chilling time was insufficient (Leida et al, 2012). These results suggest that chilling seeds at 5°C for 2 weeks was not enough to avoid dwarfism and lesions in this study.…”
Section: Id_genesmentioning
confidence: 69%
See 4 more Smart Citations
“…(1977) found that short stratification promoted the production of morphological lesions on peach leaves. An in vitro culture experiment on peach seeds showed that seedlings grew with a dwarf phenotype when the chilling time was insufficient (Leida et al, 2012). These results suggest that chilling seeds at 5°C for 2 weeks was not enough to avoid dwarfism and lesions in this study.…”
Section: Id_genesmentioning
confidence: 69%
“…In a previous study, LeMADS were also significantly repressed during chilling treatment of peach embryos (Worarad et al, 2016). Similarly, the expressions of DAM1 and DAM6 that are in the DORMANCY AS-SOCIATED MADS-box (DAM) group were decreased significantly by chilling treatment in peach seeds (Leida et al, 2012), suggesting that MADs box genes are associated with release of seed dormancy by stratification in mechanisms of transcriptional regulation. Furthermore, most of the genes encoding LEA proteins have been shown to contain ABA response (ABRE) and/or low temperature response (LTRE) elements in their promoters, and many of these genes are induced by ABA, cold, or drought stress (Hundertmark and Hincha, 2008).…”
Section: Introductionmentioning
confidence: 67%
See 3 more Smart Citations